Caricatura, censura y dictadura: los retratos cómicos de Videla (Argentina, 1976-1981) - Mara Burkart (Caravelle)
The aim of this work is to analyze dictator Jorge R. Videla’s caricatures made under his presidency by Landrú, Sábat and Cascioli, the most prominent and prolific cartoonists in Argentina and published in important mass media such as the newspaper Clarin and the magazines Tia Vicenta (second period) and HUM®. The analysis demonstrates that, under those circumstances ruled by censorship, terror and fear, the humorists lavished on the dictator, possibly for various reasons, a “cautious respect”. This changed and caricature reached a peak of great splendor with the reactivation of civil society and the regime’s collapse after the defeat in the Falklands War (Guerra de Malvinas).